DETERMINANTS OF INVASIVE VERSUS CONSERVATIVE MANAGEMENT OF CORONARY ARTERY DISEASE AT A TERTIARY CENTRE IN TAMIL NADU: A RETROSPECTIVE HOSPITAL-BASED OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Invasive management of coronary artery disease (CAD), including percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG), improves outcomes in selected patients; however, its utilization in non-metropolitan Indian tertiary centres remains variable. To estimate the proportion of CAD admissions managed invasively at a tertiary centre in Tamil Nadu and to identify independent determinants of the management decision. Materials and Methods: A retrospective hospital-based observational study was conducted among consecutive adult CAD admissions between January 2022 and December 2024. The primary outcome was management modality (invasive vs conservative). A total of 320 patients were included. Bivariate analysis and multivariable logistic regression were performed to identify determinants of invasive management. Results: Of 320 CAD admissions, 110 (34.4%) received invasive management. After multivariable adjustment, STEMI presentation (aOR 4.34, 95% CI 2.48–7.58; p